2015
DOI: 10.1016/j.stem.2015.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

m6A RNA Methylation Is Regulated by MicroRNAs and Promotes Reprogramming to Pluripotency

Abstract: N(6)-methyladenosine (m(6)A) has been recently identified as a conserved epitranscriptomic modification of eukaryotic mRNAs, but its features, regulatory mechanisms, and functions in cell reprogramming are largely unknown. Here, we report m(6)A modification profiles in the mRNA transcriptomes of four cell types with different degrees of pluripotency. Comparative analysis reveals several features of m(6)A, especially gene- and cell-type-specific m(6)A mRNA modifications. We also show that microRNAs (miRNAs) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
354
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 486 publications
(386 citation statements)
references
References 51 publications
(85 reference statements)
24
354
0
1
Order By: Relevance
“…[50] This study also reveals that m6A modification is required for the reprogramming, and can increase the reprogramming effi ciency. [50] Several genome wide association studies indicated an association between FTO gene and childhood and adult obesity. [51,52] The Over-expression of Fto increases food intake and results in obesity in mice; the mutation of Fto leads to postnatal growth retardation, signifi cant reduction in adipose tissue, lean body mass, and protects mice from obesity.…”
Section: Review Articlementioning
confidence: 67%
See 2 more Smart Citations
“…[50] This study also reveals that m6A modification is required for the reprogramming, and can increase the reprogramming effi ciency. [50] Several genome wide association studies indicated an association between FTO gene and childhood and adult obesity. [51,52] The Over-expression of Fto increases food intake and results in obesity in mice; the mutation of Fto leads to postnatal growth retardation, signifi cant reduction in adipose tissue, lean body mass, and protects mice from obesity.…”
Section: Review Articlementioning
confidence: 67%
“…[49] Another interesting study has found that m6A modification enriched at miRNA target sites, and the formation of m6A depends on Dicer, a processor of miRNA maturation. [50] The modulation of miRNAs could affect the binding of Mettl3 to mRNA, and thus affect the abundance of m6A. [50] This study also reveals that m6A modification is required for the reprogramming, and can increase the reprogramming effi ciency.…”
Section: Review Articlementioning
confidence: 84%
See 1 more Smart Citation
“…(25) and (26)), although they are heavily affected by feature representations. For example, 7 physical-chemical properties, i.e., 3 PC , 11 PC , 9 PC , 12 PC , 10 PC , 13 PC , and 21 PC are ranked among the top 11 properties in both PseDNC and AC+CC based partial order relationships. Similarly, 7 common properties, i.e., 4 PC , 5 PC , 20 PC , 1 PC , 6 PC , 17 PC , and 7 PC , appear in the last 11 properties in both partial order relationships.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) is one of the most prevalent post-transcriptional RNA modifications [1][2][3] and plays a critical role in a number of biological processes, including mRNA splicing, export, stability, immune tolerance and transcription [4][5][6][7][8][9][10]. Current researches revealed that the m 6 A modification is a dynamic and reversible process which affected the gene regulation function in apoptosis, circadian rhythm and meiosis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%